Synthesis and Spectral Studies of Some Novel Coumarin Based Disperse Azo Dyes: Studies of Coumarin Based Azo Dyes - Amjad, Rana; Munawar, Munawar Ali; Khan, Shahid Rehman; Naeem, Muhammad (Biological Sciences - PJSIR, 2009)
Synthesis of some novel coumarin based azo dyes was carried out by diazotization of heterocyclic amines using nitrosyl sulphuric acid and then coupling them with 7-hydroxy-4-methyl Coumarin. The synthesized dyes when applied on polyester fibers showed moderate to good light fastness and very good to excellent fastness to washing, rubbing, perspiration and sublimation.